Effet du Manganèse sur la Croissance de la Patate Douce (Ipomoea batatas L.) au Gabon - Lepengue, Alexis Nicaise; Nzengue, Ephrem; Mombo, Stéphane; Essougou, Christophe Yene; Ontod, Dhert Souviens Tshi-Tshi; Mokea-Niaty, Aurélien; Mbatchi, Bertrand (European Scientific Journal, ESJ, 2019)
Soil contamination in the mining town of Moanda, in southwestern of Gabon, is characterized by high concentrations of Manganese. This work aims to analyze the impact of various manganese concentrations in soils on sweet potato growth and development. The plant’s seeds were obtained on the local market. The stems were grown in greenhouses in 5 media, 4 of which were enriched with manganese and 1 not enriched. The manganiferous effect was assessed by measuring biochemical and physico-chemical parameters (total chlorophyll, dry matter, total sugars). The effects of the 5 treatments were compared on the Statistica 7.2. software from an Anova. The results show that high concentrations (25%, 50%, 75% and 100%) affect the morphometric characteristics of the sweet potato. Concentrations at 25% Mn increase the parameters and decrease them to 50% and 75% Mn, compared to the control. The 100% Mn concentrations totally inhibit the growth and development of the sweet potato. La contamination des sols de la ville miniÃ¨re de Moanda, au Sud-Est du Gabon est caractÃ©risÃ©e par de fortes concentrations de manganÃ¨se. De ce fait, ce travail vise Ã analyser lâ€™impact de diverses concentrations de manganÃ¨se dans les sols sur la croissance et le dÃ©veloppement de la patate douce. Les semences de la plante ont Ã©tÃ© obtenues sur le marchÃ© local. Les tiges ont Ã©tÃ© cultivÃ©es en serre sur 5 milieux dont 4 enrichis en manganÃ¨se et 1 non enrichi. Lâ€™effet manganifÃ¨re a Ã©tÃ© Ã©valuÃ© par la mesure des paramÃ¨tres biochimiques et physico-chimiques (chlorophylle totale, matiÃ¨re sÃ¨che, sucres totaux). Les effets des 5 traitements ont Ã©tÃ© comparÃ©s sur le logiciel Statistica 7.2. Ã partir dâ€™une Anova. Les rÃ©sultats montrent que les fortes concentrations (25% ,50%, 75% et 100%) affectent les caractÃ©ristiques morphomÃ©triques de la patate douce. Les concentrations Ã 25% de Mn entraÃ®nent une augmentation des paramÃ¨tres et une diminution de ces derniers Ã 50% et 75% de Mn, par rapport au tÃ©moin. Les concentrations Ã 100% de Mn inhibent totalement la croissance et le dÃ©veloppement de la patate douce.